Everything cat : what kids really want to know about cats - Crisp, Marty (Minnetonka, MN : NorthWord Press, 2003)
Uses a question-and-answer format to present a variety of information about cats.
Includes bibliographical references (p. 62-63).
5.3
3-6
3-6
School Library Journal
Publisher's Weekly
Keywords: Cats -- Miscellanea -- Juvenile literature; Cats -- Miscellanea; Questions and answers; Cats -- Miscellanea; Questions and answers